Ответы и объяснения

2014-02-19T20:31:07+00:00
А) =(31/5-13/3):(-4/3)=(93/15-65/15):(-4/3)=28/15:(-4/3)=-28/15*3/4=-7/5=-1 2-5

Комментарий удален
б) -11/3:3/2+5/3*3/2=-22/9+5/2=-44/18+45/18=1/18
2014-02-19T20:42:41+00:00
А) Выражение: (6*1/5-4*1/3)/(-1*1/3) Действие 1: 6/5=1.2 Действие 2: 1.2-4/3=-2/15 Действие 3: 2/15/(-1/3)=-2/15/1*3 Действие 4: 2*3=6 Действие 5: 6/15=0.4 Действие 6: -(-0.4)=0.4 Ответ: 0.4 Б)Выражение: -3*2/3/1*1/2+1*2/3*1*1/2 Действие 1: 3*2=6 Действие 2: 6/3=2 Действие 3: 2/2=1 Действие 4: 2/2=1 Действие 5: -1+1/3=-2/3 Ответ: -2/3